Informed learning applications : insights from research and practice - Ranger, Kim L. (Advances in librarianship,, 2019)
Informed Learning Applications: Insights from Research and Practice is the latest volume of rigorous research in the Advances in Librarianship series. Edited by experienced librarian Kim L. Ranger, the eight contributions to this volume describe various practices using and extending Christine Bruce's informed learning theory from a range of educational spaces, from schools to universities. Chen and Chen address integrated information literacy instruction in Taiwanese elementary schools by joining the Big6 model, inquiry-based learning, and Bruce's Six Frames. Woods and Cummins apply universal design in teaching first-year university students about the research process within the discipline of documentary filmmaking using library guides. Tucker blends informed learning with Meyer and Land's threshold concepts to redesign master's courses and uses information experience to assess students' transformed learning experiences and relationships with information. Leek and Brown train university speech center peer tutors and recommend revising public speaking communication curricula. Ranger creates a model of relational liaising by applying Bakhtinian leadership principles to academic librarianship and gives examples that combine informed learning and scholarly communication. Fundator and Maybee transform the role of librarians in higher education to "informed learning developers." Cunningham uses blended models that represents stakeholders' information literacy conceptions and perceptions of their information context to promote learning in an international school community. Whitworth and Webster observe postgraduate students as they negotiate power and authority through resistance in their online communication practices. Informed Learning Applications focuses on integrating approaches to learning, featuring librarian praxis and collaboration with disciplinary instructors. It is the ideal read for academic librarians and researchers looking to explore how to facilitate learning.